FROM MSA to CA A Beginner's Guide to Transitioning to Colloquial Arabic - Gomaa, Lina (Open textbook library., 2015)
This book is for students who have studied Modern Standard Arabic (MSA) for one year or more and would like to learn colloquial Arabic basics using their knowledge of MSA. It aims at transitioning learners from Novice Mid level to Intermediate Low through presenting situations useful for living in an Arab country. The book has several features including hyperlinks, practice dialogues with open answers, cultural tips, and more.